Unlocking the potential of TRPV1 based siRNA therapeutics for the treatment of chemotherapy-induced neuropathic pain - Akhilesh; Uniyal A.; Gadepalli A.; Tiwari V.; Allani M.; Chouhan D.; Ummadisetty O.; Verma N.; Tiwari V. (My University, 2025)
Chemotherapy-induced neuropathic pain (CINP) is among the most common clinical complications associated with the use of anti-cancer drugs. CINP occurs in nearly 68.1% of the cancer patients receiving chemotherapeutic drugs. Most of the clinically available analgesics are ineffective in the case of CINP patients as the pathological mechanisms involved with different chemotherapeutic drugs are distinct from each other. CINP triggers the somatosensory nervous system, increases the neuronal firing and activation of nociceptive mediators including transient receptor protein vanilloid 1 (TRPV1). TRPV1 is widely present in the peripheral nociceptive nerve cells and it has been reported that the higher expression of TRPV1 in DRGs serves a critical role in the potentiation of CINP. The therapeutic glory of TRPV1 is well recognized in clinics which gives a promising insight into the treatment of pain. But the adverse effects associated with some of the antagonists directed the scientists towards RNA interference (RNAi), a tool to silence gene expression. Thus, ongoing research is focused on developing small interfering RNA (siRNA)-based therapeutics targeting TRPV1. In this review, we have discussed the involvement of TRPV1 in the nociceptive signaling associated with CINP and targeting this nociceptor, using siRNA will potentially arm us with effective therapeutic interventions for the clinical management of CINP. © 2021 Elsevier Inc.